Prognosis Factors and Outcomes of Neuro-ophthalmologic Sarcoidosis. (19th May 2022) - Leclercq, Mathilde; Sené, Thomas; Chapelon-Abric, Catherine; Desbois, Anne Claire; Domont, Fanny; Maillart, Elisabeth; Shor, Natalia; Vignal-Clermont, Catherine; Guéguen, Antoine; Bodaghi, Bahram; Cacoub, Patrice; Touitou, Valerie; et al.
ABSTRACT: Background: Neuro-ophthalmologic manifestations are uncommon in sarcoidosis. We aim to assess the prognostic factors and outcome of neuro-ophthalmic sarcoidosis. Methods: We conducted a multicenter retrospective study on patients with neuro-ophthalmic sarcoidosis. Response to therapy was based on visual acuity, visual field, and orbital MRI exam. Factors associated with remission and relapse were analyzed. Results: Thirty-five patients [median (IQR) age of 37 years (26.5–53), 63% of women] were included. The diagnosis of sarcoidosis was concomitant of neuro-ophthalmologic symptoms in 63% of cases. Optic neuritis was the most common manifestation. All patients received corticosteroids and 34% had immunosuppressants. At 6 months, 61% improved, 30% were stable, and 9% worsened. Twenty percent of patients had severe visual deficiency at the end of follow-up. Nonresponders patients had significantly worse visual acuity at baseline ( p = 0.01). Relapses were less frequent in patients with retro-bulbar optic neuropathy ( p = 0.03). Conclusion: Prognosis of neuro-ophthalmic sarcoidosis is poor.